2020
DOI: 10.1073/pnas.1917549117
|View full text |Cite
|
Sign up to set email alerts
|

Conformational control of small GTPases by AMPylation

Abstract: Posttranslational modifications (PTMs) are important physiological means to regulate the activities and structures of central regulatory proteins in health and disease. Small GTPases have been recognized as important molecules that are targeted by PTMs during infections of mammalian cells by bacterial pathogens. The enzymes DrrA/SidM and AnkX fromLegionella pneumophilaAMPylate and phosphocholinate Rab1b during infection, respectively. Cdc42 is AMPylated by IbpA fromHistophilus somniat tyrosine 32 or by VopS fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The human Cdc42 1-179aa Q61L (referred to as Cdc42)-encoding DNA was cloned into a modified pGEX-4T-1 vector (GE Healthcare, Chicago, Illinois) as previously described (Barthelmes et al, 2020), resulting in a construct with a N-terminal glutathione S-transferase (GST) tag followed by the Tobacco Etch Virus (TEV) protease cleavage site. As previously described (Schoebel et al, 2009), the human Rab1b 3-174aa (referred to as Rab1b)-encoding DNA was cloned into a modified pMAL vector (New England Biolabs), resulting in a construct with a N-terminal hexahistidine (6xHis) tag, followed by maltose-binding protein (MBP) and the TEV protease cleavage site.…”
Section: Molecular Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…The human Cdc42 1-179aa Q61L (referred to as Cdc42)-encoding DNA was cloned into a modified pGEX-4T-1 vector (GE Healthcare, Chicago, Illinois) as previously described (Barthelmes et al, 2020), resulting in a construct with a N-terminal glutathione S-transferase (GST) tag followed by the Tobacco Etch Virus (TEV) protease cleavage site. As previously described (Schoebel et al, 2009), the human Rab1b 3-174aa (referred to as Rab1b)-encoding DNA was cloned into a modified pMAL vector (New England Biolabs), resulting in a construct with a N-terminal hexahistidine (6xHis) tag, followed by maltose-binding protein (MBP) and the TEV protease cleavage site.…”
Section: Molecular Biologymentioning
confidence: 99%
“…The human FICD 102-458aa E234G (referred to as FICD)-encoding DNA was cloned into a modified pMAL vector (New England Biolabs), resulting in a construct with a N-terminal 6xHis tag, followed by the HaloTag®, the TEV protease cleavage site and a Strep-tag® II. The Vibrio parahaemolyticus VopS 31-387aa (referred to as VopS)-encoding DNA was cloned into a modified pMAL vector (New England Biolabs) as previously described (Barthelmes et al, 2020), resulting in a construct with a N-terminal 6xHis tag, followed by MBP and the TEV protease cleavage site. The Histophilus somni IbpA 3483-3797aa I3455C (referred to as IbpA)-encoding DNA was cloned into a modified pSF vector (Oxford Genetics Ltd, Oxford, UK), resulting in a construct with a N-terminal decahistidine (10xHis) tag, followed by MBP, the TEV protease cleavage site and a 3xFLAG® tag.…”
Section: Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the indirect minor impact of GtgE-mediated cleavage on the switch II has a big consequence for the interaction of Rab32 with GDI resulting in the ability to bind to Rab32 cleaved :GDP and Rab32 cleaved :GTP. Recently, it has been shown that bacteria can lock Rab1b in the active state using AMPylation (Barthelmes et al, 2020). Consequently, Salmonella may use proteolysis to force Rab32 into an inactive-like conformation as demonstrated here by NMR.…”
Section: Ll Open Access Isciencementioning
confidence: 76%
“…The main effect of proximity consists in increasing the effective local concentration of the reactants to boost reaction rates and enable reactions that would not yield products in the absence of the concentration effect. To stabilise the DrrA ATase -Rab1b interface, we overexpressed various C-terminally His6-tagged Rab1b constructs (amino acids 3−174; Rab1b 3−174 with a Q67A Rab1b mutation that minimises Rab1b GTP hydrolysis) 22 , 23 bearing BrC6K at different positions (R69 Rab1b , T72 Rab1b , I73 Rab1b and R79 Rab1b ) in the vicinity of the AMPylation site (Y77 Rab1b ), together with an N-terminally Strep-tagged wild type (wt) DrrA ATase construct (amino acids 16−352; DrrA 16−352 ). Co-expression of Rab1b with BrC6K at position 69 Rab1b and wt DrrA ATase resulted in the formation of a covalently crosslinked complex, as confirmed by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) shift analysis via α-His6 and α-Strep western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%